Perancangan Sistem Mengenal Lagu Daerah Dan Lagu Wajib Nasional Berbasis Android (Studi Kasus: SDN Sindang Sari II) - Wahyudin Alipudin; Yudi Kurniawan (CV. Multi Kreasi Media, 2023)
SDN Sindang Sari II is one of the educational units with an elementary level. In carrying out its activities, SD Negeri Sindang Sari II is under the auspices of the Ministry of Education and Culture. In the implementation of the introduction of learning folk songs, the teacher conveys the learning objectives, the teacher conveys learning materials, the teacher uses the media in the core learning activities. During the learning of regional and national songs, such as paying attention when learning takes place, enjoying singing, being interested in singing and listening to regional and national songs. However, the introduction or learning is not widely understood or known by students when asked directly by individuals about regional and national songs from the creators or their lyrics, they cannot answer these questions. Therefore, the purpose of this study is to create a system to recognize regional and national songs, which can apply recognizing songs on the android operating system that was created to be an alternative application in introducing folk and national songs to increase interest in knowledge about folk songs and obligatory songs. national.